METHODOLOGICAL PRINCIPLES OF PHYSICAL EDUCATION OF STUDENTS IN EXTRA-CURRICULUM ACTIVITIES - Stadnyk, Volodymyr; Korol , Aleksandr; Grebinka, Galyna; Borovik, Yuriy (Mountain School of Ukrainian Carpaty, 2020)
. In the article the deals issues of physical education of students in extra-curriculum activities while studying in higher education institutions have been studied. The purpose of the study is to determination of methodological bases of physical education of students of university in extra-curriculum activities. The research is based on the use of a set of general scientific theoretical methods: analysis, synthesis, systematization, and generalization. That in view of the considerable problems of preserving the health of the youth on a state scale, one of the key problems is the proper organization of the students' physical-health activity in the extra-curricular time it is established. On the basis of consideration and generalization of the researches on the researched question, general theoretical foundation of the theory and methodology of physical education, own author's vision concretized and systematized information about methodological principles of physical education of students in extra-curricular activities. The idea of using anthropological, competence, axiological, activity, acmeological, differentiated and personality-oriented, systematic and innovative methodological approaches in extra-curricular forms of physical education of students to ensure the effectiveness of this process has been further developed. The principles of organization of physical education of students in extra-curriculum activities are defined, which are based on theoretical generalization of pedagogical provisions of the theory and methodology of physical education and generally didactic principles of organization of classes. That the rational organization of extra-curriculum activities on physical education of students requires observance of basic and scientific-methodical principles as general guidelines of action, which are adequate to the purpose and task in order to ensure the effective solution of their problems it is established. Information on ways of improving the efficiency of physical education of students in extra-curriculum activities was added to ensure the effectiveness of this process, according to the results of the stud.